Publication Activities of Pedagogical Universities: Quantitative and Qualitative Indicators - Kh.-A. S. Khaladov; I. V. Golovina; G. A. Paputkova (Высшее образование в России)
The article aims to study the effectiveness of teachers’ research activities at pedagogical universities. This indicator is measured by scientific publications that promote scientific research results and the dissemination of scientific flows that affect productivity and effectiveness of scientific activities at universities. The main methods of research are the quantitative analysis of the characteristics of teachers’ publication activity at pedagogical universities, the analysis of bibliometric data and their classification, statistical and comparative analysis. Within the framework of the study, a literature review is presented. The article highlights the results of the of the teachers’ publication activity analysis over the past five years and trends in the development of publication activity. The authors have also provided an analysis of the quality and the level of journals in which authors affiliated with pedagogical universities are published. In addition, the shortage of peer-reviewed journals for educational research publication is revealed. The conclusions are made about the specifics of promoting research of pedagogical universities: orientation of university teachers to publish research results in peer-reviewed journals; formation of collaborations with the leading Russian and foreign scientists or research groups for joint research. The authors also propose measures to eliminate difficulties in the teachers’ publication activities: training in the basics of legal literacy for intellectual activity results protection and promotion, as well as the formation of a support system for scientific and pedagogical staff for publishing research results in peer-reviewed journals.